Comparison of extrusion and co-extrusion encapsulation techniques to protect Lactobacillus acidophilus LA3 in simulated gastrointestinal fluids. (March 2018) - Silva, Marluci P.; Tulini, Fabrício L.; Martins, Evandro; Penning, Manfred; Fávaro-Trindade, Carmen S.; Poncelet, Denis
Abstract: This study aimed to compare two processes for the encapsulation of Lactobacillus acidophilus LA3 using alginate or a blend of alginate–shellac as the wall material and sunflower oil as the core. The particles were dried and stored for up to 60 days at 25 °C for stability studies, and the survival of the encapsulated probiotics in simulated gastrointestinal fluids was evaluated. The viability of the LA3 encapsulated by co-extrusion using alginate or a blend of alginate–shellac was, respectively, 6.2 and 7.2 log CFU/g (colony-forming units per gram), after 60 days of storage, while the viability of the LA3 encapsulated by extrusion was, respectively, 5.3 and 6.2 log CFU/g. The particles produced with the blend of alginate–shellac presented additional protection to the probiotics, as revealed by the increased survival rates in simulated gastrointestinal fluids. Taken together, these data provide a promising alternative for the incorporation of the probiotic L. acidophilus LA3 into new functional foods. Highlights: Co-extrusion increased probiotic survival by about 80% in gastrointestinal fluids. Drying the particles extended probiotic viability. Shellac is a promising natural polymer to improve particles' structure. After 60 days ca. 83% of the probiotics loaded into dried particles were viable.